Immunocytochemistry of plant cells - Vaughn, Kevin (Springer Netherlands, 2013)
Immunocytochemistry of Plant Cells is the first book exclusively dedicated to this topic. The first and largest portion of the book is concerned with a group of proven protocols and variations on these protocols that might prove useful, many developend or modified in the author's laboratory. The second portion of the book covers the studies that have been published previously on each of the plant organelles. Numerous state of the art micrographs from researchers around the world are included to demonstrate typical results.